Sejarah Rumah Baca Anak Nagari (RBAN) di Tilatang Kamang (2017-2024) - Fadila Rahmah; Kori Lilie Muslim (YASIN, 2026)
Studies on community reading centers as a means of strengthening local literacy have developed, but research that specifically examines the history, development, and contribution of Rumah Baca Anak Nagari (RBAN) in the context of rural communities remains limited. This study aims to explore the process of RBAN’s establishment and the changes that occurred during 2017–2024, while also analyzing its impact on education and the social life of the community in Tilatang Kamang. This study used a qualitative approach with a historical research method that included heuristics, source criticism, interpretation, and historiography. Data were collected through interviews with the founder, managers, and visitors, as well as documentation of activities and book borrowing. The results showed that RBAN experienced significant development in physical aspects, management, and programs, with the number of book collections increasing from 500 copies at the beginning of its establishment to more than 10,000 copies in 2024. RBAN also succeeded in expanding its facilities and adding various literacy programs, although it still faced challenges in funding and physical management. These findings indicate that RBAN plays an important role in increasing the community’s interest in reading and contributes to the educational and social fields for children, school students, university students, educators, and the general public. The conclusion of this study emphasizes that the existence of RBAN functions not only as a community reading center, but also as a space for social literacy that contributes to improving the quality of education and the social life of rural communities. This study enriches the literature on social literacy and the management of community reading centers and opens space for the development of similar models in other local contexts.